VERTICAL ZONALITY OF FISH DISTRIBUTION IN THE UPPER BATHYAL OF THE SEA OF OKHOTSK(Vertikalnaya Zonalnost v Raspredelenii Ryb v verkhnei Batiali Okhotskogo Morya) - Shuntov,V. P. (1968)
Within the upper bathyal of the Okhotsk Sea several fish groups are distinguished, whose distribution peculiarities are determined by that of water masses. An analysis of the distribution of several dozens of fish species shows the most drastic change in the species composition at the border line of water masses (200 and 600m). At depts below 600-700m, fish fauna is very improverished due to oxygen deficiency in these horizons. The problem of fish stock supply within the bathyal of the Okhotsk Sea is discussed. The complex of unfavorable factors (extreme severity of sea, the character of the current system, low biomas of benthos) is responsible for a low population of benthophages as well as of planktonphages and predators. (Author) Trans. of Zoologicheskii Zhurnal (USSR) v44 n11 p1678-1689 1965, by M. Slessers.